THE ROLE OF MUSLIM SCHOLARS IN MINIFYING RELIGIOUS EXTREMISM FOR PEACE BUILDING AND EDUCATIONAL DEVELOPMENT IN NIGERIA - Mukhtar, Sarkin (PEOPLE: International Journal of Social Sciences, 2018)
Insurgency, religious extremism and other related religious crises become hydra-headed in Nigeria, which cause destruction of human lives and properties worth billions of naira, millions people were displaced and many school-going age are out of school. The Boko Haram terrorism is one of insecurity challenges in Northern Nigeria, which has negative impact on Nigerian education seriously and forced many children to abandoned schools in an already ill-educated region. The wrong teachings and misinterpretations of Islam by some Muslims fuel the spread of extremist ideologies and emergence of extremist groups. A multi-religious country like Nigeria to realise its development in all human aspects there must be unity and religious tolerance. Many agreed that changing the ideologies of insurgents and religious extremism will require intellectual role. Muslim scholars can play a vital role in promoting social reform and peace co-existence. This paper discusses the importance of unity among Muslims and non-Muslims community. The paper also reviews the relationship among Muslims and non-Muslims during the time of the Prophet (S.A.W.). The consequences of religious extremism, terrorism, sectarians and intolerance on education are examined. To minify religious intolerance and extremism the paper identifies the roles to be played by Muslim scholars. The paper concludes that to realise Nigerian educational goals and objectives and to ensure education for all Muslim should shun away from any religious crises and embrace unity and religious tolerance. Finally, the paper recommends among others that only pious and learned scholars should be allowed to preach, Muslim should be patient, tolerance in dealing with Muslims and non-Muslims. National and international organisations should cooperate in reconstruction and maintenance of schools in recovered affected areas from Boko haram insurgency.